Whole-body vibration as a passive alternative to exercise after myocardial damage in middle-aged female rats: Effects on the heart, the brain, and behavior - Tóth, Kata; Oroszi, Tamás; Nyakas, Csaba; van der Zee, Eddy A.; Schoemaker, Regien G. (Frontiers in Aging Neuroscience, 2023)
Females with cardiovascular disease seem more vulnerable to develop concomitant mental problems, such as depression and cognitive decline. Although exercise is shown beneficial in cardiovascular disease as well as in mental functions, these patients may be incapable or unmotivated to perform exercise. Whole body vibration (WBV) could provide a passive alternative to exercise. Aim of the present study was to compare WBV to exercise after isoproterenol (ISO)-induced myocardial damage in female rats, regarding effects on heart, brain and behavior. One week after ISO (70 mg/kg s.c., on 2 consecutive days) or saline injections, 12 months old female rats were assigned to WBV (10 minutes daily), treadmill running (30 minutes daily) or pseudo intervention for 5 weeks. During the last 10 days, behavioral tests were performed regarding depressive-like behavior, cognitive function, and motor performance. Rats were sacrificed, brains and hearts were dissected for (immuno)histochemistry. Significant ISO-induced cardiac collagen deposition (0.67± versus 0.18±0.03%) was absent after running (0.45±0.26 versus 0.46±0.08%), but not after WBV (0.83±0.12 versus 0.41±0.05%). However, WBV as well as running significantly reduced hippocampal (CA3) collagen content in ISO-treated rats. Significant regional differences in hippocampal microglia activity and brain derived neurotrophic factor (BDNF) expression were observed. Significant ISO-induced CA1 microglia activation was reduced after WBV as well as running, while opposite effects were observed in the CA3; significant reduction after ISO that was restored by WBV and running. Both WBV and running reversed the ISO-induced increased BDNF expression in the CA1, Dentate gyrus and Hilus, but not in the CA3 area. Whereas running had no significant effect on behavior in the ISO-treated rats, WBV may be associated with short-term spatial memory in the novel location recognition test. Although the female rats did not show the anticipated depressive-like behavior or cognitive decline after ISO, our data indicated regional effects on neuroinflammation and BDNF expression in the hippocampus, that were merely normalized by both WBV and exercise. Therefore, apart from the potential concern about the lack of cardiac collagen reduction, WBV may provide a relevant alternative for physical exercise.